Thermal behavior of lithium‐ion battery in microgrid application: Impact and management system. (22nd November 2020) - Hasani, Azri H.; Mansor, Muhamad; Kumaran, Vigna; Zuhdi, Ahmad W. M.; Ying, Yong J.; Hannan, Mahammad Abdul; Hamid, Fazrena A.; Rahman, Muhamad S. A.; Salim, Nur A.
Summary: Safe and reliable operation is among the considerations when integrating lithium‐ion batteries as the energy storage system in microgrids. A lithium‐ion battery is very sensitive to temperature in which it is one of the critical factors affecting the performance and limiting the practical application of the battery. Furthermore, the adverse effects differ according to the temperature. The susceptibility of lithium‐ion battery to temperature imposes the need to deploy an efficient battery thermal management system to ensure the safe operation of the battery while at the same time maximizing its performance and life cycle. To design a good thermal management system, accurate temperature measurement is vital to assist the battery thermal management system in managing relevant states such as the stage‐of‐charge and state‐of‐health of the battery. This article outlines the effects of low and high temperatures on the performance of Li‐ion batteries. Next, a review of currently available internal temperature monitoring approaches is presented based on their feasibility and complexity. Then, an overview of battery thermal management systems based on different cooling mediums is presented. This includes air cooling, liquid cooling, phase change material (PCM) cooling, heat pipe cooling, boiling‐based cooling, and solid‐state cooling. The final section of this article discusses the practical implementation of the internal temperature measurement approach and battery thermal management system for microgrids. From the review, a suitable candidate is the flexible, low maintenance, and long lifetime hybrid battery thermal management system that combines heat pipe cooling and solid‐state cooling. It is capable of maintaining the maximum operating temperature of the battery within 45°C at up to 3C discharge rate while being a relatively simple system. Additionally, passive PCM with thermally conductive filler can also be employed to assist the hybrid battery thermal management system in improving the temperature uniformity well within 5°C. Abstract : Second‐life lithium‐ion batteries are used in the microgrid to extend their useful life, where these batteries are expected to generate more heat than their new counterparts. Additionally, further abuse by charging/discharging the batteries at high rates impose safety risk associated with fire and explosion. This review article outlines the adverse effects of temperature, followed by approaches used to monitor the internal battery temperature, and finally currently available battery thermal management systems that are possible candidates for microgrid application.